Internal combustion engine acoustic diagnostics - V. D. Gabidulin (Вестник СибАДИ)
Introduction. To ensure stable performance of transport and technological machines, constant monitoring of their technical condition is necessary. Timely diagnosis is difficult to carry out when working in remote regions, as well as when transporting goods over long distances due to the lack of closely located maintenance centers.Materials and methods. One of the solutions to the above problem is the use of a diagnostic method based on sound parameters. In particular, this method is applicable to power plants. Its advantage is the ability to quickly assess the condition of the engine mechanisms and systems on site using a portable device (without the use of large-sized and low-mobility equipment) by non-destructive testing. Thus, the research and implementation of the acoustic diagnostic method is promising and in demand today. One of the most important areas for improving power plants today is the automation of control processes for their operation based on the use of electronics and microprocessor systems. With a positive effect on the efficiency of the engine, these complex systems expand the range of its potential malfunctions. The purpose of this study was to evaluate the fundamental possibility of determining and comparing the acoustic parameters of an engine with and without violations of the operating mode in the event of failures in electronic control systems of its operation. As an example, the Ford Focus passenger car was chosen as the object of the study. A malfunction in the electronic ignition module was used as a test fault. The obtained spectral patterns of the sound radiation of the internal combustion engine (with and without violations of the operating mode) enable to determine the nature of the engine malfunction by sound parameters.Results. A frequency range at which it is possible to identify the spectral pattern of an engine with impaired operation and an engine without impaired operation was obtained. This range was 6,000-6,500 Hz, since in this segment the sound level reaches more than 40 dB.Discussions and conclusions. The conducted experiment is the initial stage of a large-scale experimental study, the result of which will serve as a starting point for the introduction of the acoustic method into the process of diagnosing electronic control systems for internal combustion engines.